En Coup de Sabre: A Classical Case of Linear Morphea in a Young Woman - Nanda Earlia; Arie Hidayati; Cut Yunita; Fitri Dewi Ismida; Wizurai Wisesa (Indonesian Journal of Case Reports, 2026)
Morphea, or localized scleroderma, is a rare inflammatory disorder characterized by cutaneous sclerosis without systemic involvement. The craniofacial variant, en coup de sabre, is clinically significant due to its potential for deep-tissue extension and neurologic associations. A 22-year-old woman presented with a 10-year history of a progressively widening linear depressed lesion on the forehead. Clinical evaluation showed a well-demarcated atrophic plaque, while laboratory tests, including ANA, were normal. Histopathology revealed thickened collagen bundles with perivascular lymphocytic infiltration, consistent with sclerotic-phase linear morphea. The patient was diagnosed with linear morphea en coup de sabre and treated with methotrexate and corticosteroids, resulting in clinical improvement after 4 weeks. This case highlights the delayed presentation and slow progression of adult-onset craniofacial linear morphea. Despite minimal inflammatory activity, the lesion location carries a risk of deeper involvement, warranting early systemic immunomodulatory therapy. Adult-onset linear morphea en coup de sabre should be recognized in patients with slowly progressive linear atrophic forehead lesions. Early diagnosis and timely systemic treatment are essential to prevent progression and long-term deformity.